Desenvolvimento de ferramentas de bioinformática para montagem e prospecção de genomas selvagens visando o melhoramento de arroz - Farias, Daniel da Rosa (2013)
Rice is the most important grain in terms of economic value in the world, this crop has a significance to developing countries, both the culture aspect, as social and economic point. Rice is considered one of the best foods, with better nutritional balancing, extremely versatile, it is adapted in different soils and climates, this specie has greatest potential to increase the food production to control the world hunger. Despite the contribution that molecular markers gave for plant breeding, the increase of genome and transcriptome sequence data, the plant breeding approaches have greatly advanced. With this fact Bioinformatic becomes an essential tool for studies with genomic data. The principal aim of this study is to generate a tool that can contribute with assembly researches, and the assembly of Oryza glumaepatula genome. The first chapter is a review of rice, both on the cultivated species such as wilds. The second chapter presents the AEROS, a tool that aim provides the evaluation and comparison of genome assemblers, providing inferences about the results of these programs. The third chapter presents de assembly of the wild rice specie Oryza glumaepatula. With this study, we development AREOS program, that simulates a reference sequence and reads from Illumina platform. The draw assembly of Oryza glumaepatula genome has 292,860 scaffolds, and 412M bases.